(untitled) (Proceedings of Voronezh State University. Series: Geology, 2024)
Introduction: Weathering crusts contain almost all the reserves of bauxite and kaolinite, about 80 % of silicate nickel, about 50 % of high-grade iron ores, and manganese of all discovered reserves. They also accumulate Au, REE, U, Ti, Zr, phosphorites, and other types of minerals. The accumulation of minerals depends on the presence of a valuable element and the form of its presence in the parent rock. The content of various elements in the parent rock can vary from one hundredths (REE) to 20 or more (Fe) percent. Types of minerals in weathering crusts have been studied in many publications, including by the authors of the article. However, there have not been enough studies dedicated to the correlation between minerals and weathering crusts of various climatic zones and the connection between their accumulation and certain types of relief of the weathering crust. No special attention has been paid to the distribution of valuable elements along the weathering crust profile, i.e., in which zones of the weathering profile a particular type of mineral tends to be present. This article is devoted to these unresolved issues. This is the first of the series of three articles dedicated to the minerageny of Fe, Al, Mn. The second part will be devoted to other metals (Ni, Co, Au, REE, etc.), and the third to non-metals (kaolinites, phosphorites, zeolites, etc.). Methodology: In this article, the authors used their own data related to the study of a number of minerals in weathering crusts (bauxites, kaolinites, high-grade iron ores, siliceous raw materials, and zeolites). The methods of the study included formational, facies, paleogeographic, and comparative lithological methods, as well as a stadial analysis based on a detailed study of the material composition of the rocks in the weathering crusts. Stadial analysis was used due to the examination of rocks belonging to various zones of the weathering profile. We also considered the tectonic factor acting through the relief. The epigenetic processes responsible for the enrichment or depletion of the valuable element in the weathered rocks was also taken into account. Results and discussion: The first accumulations of high-grade iron ores appeared in the middle of the Devonian. At first, their average thickness was no more than 10 m in areal crusts and up to 20–30 m in linear crusts. In the Carboniferous and Mesozoic, the thickness of the areal weathering crusts was the first tens of meters, the thickness of the linear crusts was the first hundreds of meters, and in the Cenozoic, they were 50–60 and up to 300 and more, respectively. However, younger and older weathering crusts could overlap. For example, it was proved that the Kursk Magnetic Anomaly has the illite-kaolinite weathering crusts of the Devonian, and possibly even earlier ones, with developed eluvium composed of sesquioxides. The formation of increased concentrations of iron began in the zone of initial decomposition, and its greatest amount formed in the zone of final decomposition (sesquioxides) and Cuirasse. However, the impact of organic matter increasing over time was of great importance, which influenced the increase in the discove- red reserves of high-grade iron ores, which were larger in the Cenozoic than in all previous periods. Bauxites appeared in the early Paleozoic. They are karst, developed in carbonate strata, few in number, and are not yet of industrial interest. In the Middle Devonian, due to the appearance of vegetation on land and its influence on the weathering processes, which resulted in an increase in their intensity, the first deposits of high-quality bauxite appeared in weathering crusts in carbonate rocks, which contained significant quantities of an aluminosilicate component (marls, interlayers of clay, and volcanogenic material). In the Carboniferous, the intensity of weathering and the spectrum of parent rocks expanded. A sublateritic type of bauxites appeared, which differed from the typical lateritic bauxites by the presence of a complete weathering profile with 4 zones, in which bauxites were found in its uppermost part. In the Mesozoic, the alumina tended to accumulate in mobile belts with prevailing karst bauxites. In the Precambrian and young platforms, the processes of the weathering of aluminosilicate rocks mainly led to the formation of kaolinites. The absolute majority of deposits and the main global reserves of bauxite formed in the Cenozoic. They were mainly laterites; skarn deposits continued to form in mobile belts. The formation of manganese ores in weathering crusts was associated with the active biogeochemical activity of the element, its greater mobility compared to iron and aluminium, and valence changes. This, in some cases, led to its loss in the rocks of the weathering profile, and in others to its concentration. This behavior of Mn contributed to the accumulation of tens of percent at a small clarke number (0.95). In the early Paleozoic, manganese ores of the karst type were determined by abiogenic processes. Later, the influence of organic matter on weathering processes became one of the main factors and Mn deposits began to form not only in carbonate, but also in silicate rocks with an increased content of this element. Conclusion: The formation of minerals occurred at different stages of the weathering crust formation. For iron, it began in the zone of initial decomposition and reached its maximum in the zone of final decomposition. Alumina, which is part of bauxites, accumulated only in the uppermost zone of the sesquioxides of the weathering profile. The peak of manganese accumulation was within the zone of intermediate decomposition, where its ores contained inclusions of kaolinite clays.